2013
DOI: 10.1161/strokeaha.113.002217
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Headache Influences Long-term Prognosis After Acute Cerebral Ischemia of Noncardioembolic Origin

Abstract: Background and Purpose-Acute cerebral ischemia is frequently associated with headache. It is unknown whether concomitant headache reflects a partly different pathogenesis, and thus, may influence long-term prognosis after stroke. Here, we compared the long-term risk of recurrent vascular events in patients in whom a transient ischemic attack or minor ischemic stroke of noncardioembolic origin was associated with headache with those without headache. Methods-We used data from the Life Long After Cerebral ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…That is why our results showed that post-stroke headache was more likely to occur within the first seven days post-stroke. These results were in agreement with a previous study, which revealed that post-stroke headache occurred mostly within the first 3-4 days post-stroke [19]. This could be also explained by the endothelial release of bradykinins, prothrombotic factors, glutamate, interleukin-6, nitric oxide metabolites, calcitonin gene-related peptides, substance P, and excitotoxic substances during the acute phase of ischemic stroke [13,18].…”
Section: Discussionsupporting
confidence: 93%
“…That is why our results showed that post-stroke headache was more likely to occur within the first seven days post-stroke. These results were in agreement with a previous study, which revealed that post-stroke headache occurred mostly within the first 3-4 days post-stroke [19]. This could be also explained by the endothelial release of bradykinins, prothrombotic factors, glutamate, interleukin-6, nitric oxide metabolites, calcitonin gene-related peptides, substance P, and excitotoxic substances during the acute phase of ischemic stroke [13,18].…”
Section: Discussionsupporting
confidence: 93%
“…This prospective cohort with 2473 patients monitored over a median period of 14.1 years observed a lower chance of vascular death in these patients (adjusted HR 0.73; 95% CI 0.68‐0.91). However, in this same study, the chance of a cerebrovascular event and myocardial infarction reoccurring was similar between the groups with and without headache . This cohort study was not originally designed to assess headache as a prognostic factor.…”
Section: Headache Related To Ischemic Stroke As a Marker Of Severitymentioning
confidence: 99%
“…However, in this same study, the chance of a cerebrovascular event and myocardial infarction reoccurring was similar between the groups with and without headache. 44 This cohort study was not originally designed to assess headache as a prognostic factor. In addition, only minor ischemic strokes were included, which compromises its generalizability.…”
Section: Headache Related To Ischemic Stroke As a Marker Of Severitymentioning
confidence: 99%
“…The prevalence of headache in the larger systematic review was within the range found in the meta-analysis. 4,6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ICHD-3 defines HAIS as either acute or persistent and if "headache has developed in very close temporal relation to other symptoms and/or clinical signs of ischemic stroke, or has led to the diagnosis of ischemic stroke." e61 Of the 16 studies that described the timing of headache assessment, 12 studies evaluated headache within 3-4 days of stroke symptoms, 6,15,20,22-25,30,35,49,e55,e57 and the remaining 4 within 8-14 days.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Prior studies report a wide range of prevalence of headache associated with ischemic stroke. [4][5][6] New-onset headache presenting at the time of acute ischemic stroke is a predictor of persistent headache 6 months after the stroke. 7 Indeed, headache after stroke has been characterized as a common form of chronic poststroke pain.…”
mentioning
confidence: 99%